1990
DOI: 10.1002/food.19900340404
|View full text |Cite
|
Sign up to set email alerts
|

Use of oyster shell as calcium supplement. Part 2. An assessment of the responses of hepatic and serum enzymes, relative organ weights, and bone mineralization in the broiler chicken fed gossypol‐containing cottonseed cake supplemented with oyster shell

Abstract: The role of oyster shell as calcium supplement in the utilization of gossypol-containing cottonseed cake (CSC) was assessed using Hypeco broiler chickens. The results showed that of the organ measured, only the relative weight of the spleen was significantly (P less than 0.05) decreased by oyster shell supplementation in the CSC diets. Spleen weight correlated negatively (r = -0.45) with dietary calcium. Alkaline phosphatase activity in the liver was significantly (P less than 0.05) increased due to the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Active bone growth is accompanied by increased activity of bone-ALP in the plasma, and after completion of skeletal development, the level of this enzyme decreases quickly (Price, 1993). Of relevance to the present study, note that ALP activity increased dramatically in the blood of domestic hen Gallus domesticus chicks fed excessive calcium carbonate (Ogura, 1981;Aletor & Aturamu, 1990).…”
Section: Introductionmentioning
confidence: 78%
“…Active bone growth is accompanied by increased activity of bone-ALP in the plasma, and after completion of skeletal development, the level of this enzyme decreases quickly (Price, 1993). Of relevance to the present study, note that ALP activity increased dramatically in the blood of domestic hen Gallus domesticus chicks fed excessive calcium carbonate (Ogura, 1981;Aletor & Aturamu, 1990).…”
Section: Introductionmentioning
confidence: 78%
“…Such supplements were reported to have a positive impact on animal bones and the strength of eggshells [394]. In addition, different studies indicated that both oyster and clam shells are equally effective regarding eggshell strength and egg production rate [395][396][397][398][399]. Such benefits of shell derived CaCO 3 , shown in earlier studies, were also confirmed in recent research [400,401].…”
Section: Patentsmentioning
confidence: 72%
“…For example, EGGUM [9] and TEWE [ 131 reported a linear correlation between dietary protein quality and total serum protein (TSP) and stated further that like TSP, serum area and creatinine may be used as indirect measures of dietary protein quality. Similarly, ALETOR et al [2] observed that changes in alkaline phosphatase activity may be a direct response to changes in dietary Ca or changes in dietary Ca : P ratio. The efficient mineralization of the bones is influenced, not only by the absolute levels of dietary Ca and P, but also by their relative amounts in the diet.…”
Section: Introductionmentioning
confidence: 93%